THE EFFECT OF PRENATAL YOGA ON BACK PAIN IN PREGNANT WOMEN IN THE THIRD TRIMESTER - Camalia, Noor; Sukesi, Sukesi; Pipitcahyani, Tatarini Ika; Harumi, Ani Media (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
Back pain is a common occurrence in pregnant women and will increase when the mother enters the third trimester. One effort to reduce back pain experienced by pregnant women is to do prenatal yoga. Prenatal yoga can help pregnant women to stretch their joints and to relax the mother's body and mind during pregnancy. This study aims to determine the effect of prenatal yoga on back pain experienced by pregnant women in the third trimester. This type of research is Quasi-experimental design with a pre-test and post-test control group approach. The population in this study were 35 respondents of pregnant women in the third trimester at the Anugrah Surabaya Pratama Clinic, the research sample was 32 respondents. The sampling technique used purposive sampling. The Bourbannais pain scale was used as a research tool. Based on the results of the Wilcoxon Sign Rank Test, a p-value of 0.001 was obtained, which means that there is an effect of prenatal yoga on back pain in pregnant women in the third trimester. Based on the results of the Mann-Whitney U Test, a p-value of 0.007 was obtained, which means that there is a difference in the level of back pain scale in pregnant women in the third trimester at the Anugrah Surabaya Pratama Clinic. Further research is expected to be used as a reference for comparison by expanding the population and variables and replacing the comparison group with other better media.